2006
DOI: 10.1111/j.1365-2273.2006.01341_11.x
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between blood group O and epistaxis?

Abstract: Objectives.  Blood group O is associated with lower expression of von Willebrand factor 2, although the clinical significance of this is unclear. Earlier work demonstrated lower admission rate for epistaxis among Asians compared with Caucasians in our unit (P < 0.01) 1, with one of the possible explanations being higher prevalence of blood group O among Caucasians. This study investigates whether blood group O is over‐represented in patients admitted with epistaxis. Method.  Retrospective comparison of blood g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Explanations include the variability between different laboratories, patients with blood group O with low vWF levels that normalized with increasing age (15 of the 18 historical VWD cases had blood group O) or changing diagnostic criteria over time. Sixty‐five percent of patients were blood group O (Table ), which has recently been found in the Vienna Bleeding Biobank (VBB) to be associated with the diagnosis of a bleeding disorder and previously been described in association with bleeding from a range of causes , . TxA and desmopressin and rarely platelet transfusion were successful in more than 90% of cases at reducing bleeding complications when given as haemostastic prophylaxis preprocedure; 16 of 69 procedures were high bleeding risk and no abnormal bleeding was observed (Table ) .…”
Section: Discussionmentioning
confidence: 98%
“…Explanations include the variability between different laboratories, patients with blood group O with low vWF levels that normalized with increasing age (15 of the 18 historical VWD cases had blood group O) or changing diagnostic criteria over time. Sixty‐five percent of patients were blood group O (Table ), which has recently been found in the Vienna Bleeding Biobank (VBB) to be associated with the diagnosis of a bleeding disorder and previously been described in association with bleeding from a range of causes , . TxA and desmopressin and rarely platelet transfusion were successful in more than 90% of cases at reducing bleeding complications when given as haemostastic prophylaxis preprocedure; 16 of 69 procedures were high bleeding risk and no abnormal bleeding was observed (Table ) .…”
Section: Discussionmentioning
confidence: 98%
“…Levels within the upper 10% (> P90) of the population distribution of the procoagulant factors prothrombin, factor VIII, FIX, and FXI, and low levels of anticoagulation proteins, are associated with an increased risk of venous thrombosis [1][2][3][4][5]. Many preanalytic variables may affect the accuracy of these assays, including the duration of time from venipuncture to specimen processing and storage [6,7]. Clinic-based research settings are able to minimize the time from venipuncture to blood processing.…”
Section: Disclosure Of Conflict Of Interestsmentioning
confidence: 99%
“…Berg found that, in a series of patients admitted to hospital for bleeding duodenal ulcer, the mean age at onset for patients with blood group O was significantly lower than that for patients with blood group A [6]. Interestingly, in a retrospective analysis of 1261 Caucasians admitted with epistaxis, Reddy et al [7] found that subjects with group O were over-represented compared with the control population. In addition, Leonard et al [8], in a retrospective study of 303 Irish patients suffering secondary post-tonsillectomy hemorrhage, observed a disproportionately high prevalence of blood group O compared with that in the general population and concluded that a non-casual blood group-related bleeding predisposition was present in this group of surgical patients.…”
mentioning
confidence: 99%
“…11 Earlier it has been reported that blood group O was over represented in Caucasian patients admitted with epitasis, compared with the Caucasian population in general. 12 One study revealed that bleeding time was significantly longer in people with blood group O than people with non-O blood group and this could not be correlated with sex ratio, platelet count or haematocrit. 13 It is also suggested by authors that blood group O is associated with lower expression of Von Willebrand factor causing a relative bleeding tendency but other workers could not find out any association between the level of Von Willebrand factor and bleeding time.…”
Section: Introductionmentioning
confidence: 99%